Effect of species-specific differences in chromosome morphology on chromatin compaction and the frequency and distribution of RAD51 and MLH1 foci in two bovid species: cattle (Bos taurus) and the common eland (Taurotragus oryx) - Sebestova, Hana; Vozdova, Miluse; Kubickova, Svatava; Cernohorska, Halina; Kotrba, Radim; Rubes, Jiri (Chromosoma, 2016)
Meiotic recombination between homologous chromosomes is crucial for their correct segregation into gametes and for generating diversity. We compared the frequency and distribution of MLH1 foci and RAD51 foci, synaptonemal complex (SC) length and DNA loop size in two related Bovidae species that share chromosome arm homology but show an extreme difference in their diploid chromosome number: cattle (Bos taurus, 2n = 60) and the common eland (Taurotragus oryx, 2nmale = 31). Compared to cattle, significantly fewer MLH1 foci per cell were observed in the common eland, which can be attributed to the lower number of initial double-strand breaks (DSBs) detected as RAD51 foci in leptonema. Despite the significantly shorter total autosomal SC length and longer DNA loop size of the common eland bi-armed chromosomes compared to those of bovine acrocentrics, the overall crossover density in the common eland was still lower than in cattle, probably due to the reduction in the number of MLH1 foci in the proximal regions of the bi-armed chromosomes. The formation of centric fusions during karyotype evolution of the common eland accompanied by meiotic chromatin compaction has greater implications in the reduction in the number of DSBs in leptonema than in the decrease of MLH1 foci number in pachynema.
Keywords: Gene Expression Regulation; Cattle; druhová specificita; Male; SCP3; Synaptonemal Complex; skot; Recombination; Spermatocyte; RAD51; Antelopes; synaptonemální komplex; sbalení DNA; Meiosis; mužské pohlaví; Synaptonemal complex; dvouřetězcové zlomy DNA; savčí chromozomy; DNA Breaks, Double-Stranded; Species Specificity; Rad51 Recombinase; DNA Packaging; rekombinasa Rad51; antilopy; meióza; Animals; enzymy opravy DNA; MLH1; Chromosomes, Mammalian; zvířata; regulace genové exprese; Recombination, Genetic; rekombinace genetická; DNA; Immunofluorescence; DNA Repair Enzymes